Pengaruh Sikap Tenaga Kesehatan, Fasilitas Dan Harga terhadap Kepuasan Pasien - Wulandari, Novia Ika (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
This study aims to analyze Patient Satisfaction at Semarang Essential Clinic. This study uses variables of Health Worker Attitude, Facilities, Prices to analyze the effect of Patient Satisfaction. The population in this study was patients who sought treatment at Semarang Essential Clinic. Data collection was carried out by Purposive Sampling, Accidental Sampling methods and the number of samples was 97 respondents. Data collection techniques using questionnaires. The data analysis used is validity test and reliability test, classical assumption test, hypothesis test and multiple linear regression. Data processing tools using SPSS 26.0 for Windows. The results showed that the attitude of health workers (X1) had no effect and was not significant on patient satisfaction (Y) with a calculated value of 0.882 < table 1.66123 with a significance level of 0.413, Facilities (X2) had a positive and significant effect on patient satisfaction (Y) with a calculated value of 3.465 > table 1.66123 with a significance level of 0.001, and Price (X3) had a positive and significant effect on patient satisfaction (Y) with a calculated value of 4.903 > table 1.66123 with a significance level of 0.000. Keywords : Health Worker Attitude, Facilities, Price, Patient Satisfaction